Tingkat Kesejahteraan Masyarakat Nelayan Kelurahan Pohe Kecamatan Hulonthalangi Kota Gorontalo - Antu, Yulinda R.; Erlansyah, Erlansyah; Mohamad , Abdurahman Kano (Fakultas Perikanan UCM, 2025)
The welfare of fishing communities is defined as the socio-economic status of coastal populations whose livelihoods are predominantly reliant on marine resources. Pohe Village exemplifies such a community, endowed with considerable coastal resource potential that presents favorable prospects for local fishermen. This study seeks to evaluate the welfare level of the fishing community in Pohe Village, located in Hulonthalangi District, Gorontalo City. A qualitative research methodology was adopted, with data presented in both descriptive narrative and visual forms. The study employed a combination of primary and secondary data sources. Sampling was carried out using purposive sampling, wherein respondents were intentionally selected based on specific criteria aligned with the research objectives. Data analysis was conducted through tabulation techniques, based on responses obtained from questionnaires distributed to members of the local fishing community. The measurement of welfare levels was guided by the indicators set forth by the Central Statistics Agency (Badan Pusat Statistik/BPS). The results reveal that the welfare level of the fishing community in Pohe Village falls within the moderate category, with an average score of 2. The distribution of respondents according to welfare classification is as follows: 7 respondents (23.33%) were categorized as having a high level of welfare, 20 respondents (66.67%) were in the moderate category, and 3 respondents (10%) were classified as having a low level of welfare.